2010
DOI: 10.1002/pssb.201000237
|View full text |Cite
|
Sign up to set email alerts
|

Raman diagnostics of multi‐wall carbon nanotubes with a small wall number

Abstract: Raman spectroscopy study of multi‐wall carbon nanotubes (MWNTs) of different diameters (with a small controllable number of walls) produced using Fe–Co catalyst with a variable size of the same active component has been performed. We have characterized as produced MWNTs with different diameters (series 1) and two types of tubes with fixed mean diameters (∼10 and 20 nm) heated in a flow of pure argon at various temperatures (2200, 2600 and 2800 °C – series 2). The Raman spectra of MWNTs have been registered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 5 publications
3
24
1
1
Order By: Relevance
“…The HRTEM images showed that the annealing temperature 2200 o C considerably improved the outer layers but was sometimes was not enough to eliminate all the defects of the inner walls. The gradual structural development of MWNTs with annealing temperature increase was also confirmed by Raman-spectroscopy 34 which showed the increase of the relative intensities of 2D and D peaks (I2D/ID) with the increased annealing temperature testifying the systematic structural improvement of MWNT wall regularity. The temperature and field dependences of conductivity measurements of annealed MWNTs corroborate with the above findings.…”
Section: Experimental and Resultsmentioning
confidence: 70%
“…The HRTEM images showed that the annealing temperature 2200 o C considerably improved the outer layers but was sometimes was not enough to eliminate all the defects of the inner walls. The gradual structural development of MWNTs with annealing temperature increase was also confirmed by Raman-spectroscopy 34 which showed the increase of the relative intensities of 2D and D peaks (I2D/ID) with the increased annealing temperature testifying the systematic structural improvement of MWNT wall regularity. The temperature and field dependences of conductivity measurements of annealed MWNTs corroborate with the above findings.…”
Section: Experimental and Resultsmentioning
confidence: 70%
“…The first overtone of the D band (2D band) is usually found at ≈2715 cm −1 , is always present for CNT Raman spectra and its intensity tends to increase with graphitization [43]. Moreover, as it has been shown recently, carbon defects are clearly manifested by analyzing the ratio of intensitiy I 2D /I D [44]. It has been demonstrated that the 2D/D ratio intensity is increased with the decrease in the defectiveness of carbon which occurs when the nanotube diameter increases [44,45].…”
Section: Fabrication Of Samples and Experimental Detailsmentioning
confidence: 92%
“…The high crystallinity of AD-MWNTs should show up in the Raman spectra as a weak D-band, which is associated with disorder in graphitic materials [1,30]. In a nice work on Raman spectroscopy of bulk CVD MWNT material [31], it was shown that a high temperature treatment (2800…”
Section: Raman Spectra Of Individual Mwntsmentioning
confidence: 99%